Dual‐Screened Vertical Circulation Wells for Groundwater Lowering in Unconfined Aquifers. Issue 1 (19th March 2015) - Jin, Yulan; Holzbecher, Ekkehard; Sauter, Martin
Abstract: A new type of vertical circulation well (VCW) is used for groundwater dewatering at construction sites. This type of VCW consists of an abstraction screen in the upper part and an injection screen in the lower part of a borehole, whereby drawdown is achieved without net withdrawal of groundwater from the aquifer. The objective of this study is to evaluate the operation of such wells including the identification of relevant factors and parameters based on field data of a test site and comprehensive numerical simulations. The numerical model is able to delineate the drawdown of groundwater table, defined as free‐surface, by coupling the arbitrary Lagrangian–Eulerian algorithm with the groundwater flow equation. Model validation is achieved by comparing the field observations with the model results. Eventually, the influences of selected well operation and aquifer parameters on drawdown and on the groundwater flow field are investigated by means of parameter sensitivity analysis. The results show that the drawdown is proportional to the flow rate, inversely proportional to the aquifer conductivity, and almost independent of the aquifer anisotropy in the direct vicinity of the well. The position of the abstraction screen has a stronger effect on drawdown than the position of the injection screen. The streamline pattern depends strongly on the separation length of the screens and on the aquifer anisotropy, but not on the flow rate and the horizontal hydraulic conductivity.